How to Manage Your GP Practice. - Clarke, Farine (John Wiley & Sons, 2011)
The business side of running a medical practice may be unappealing but it's crucialHow to Manage Your GP Practice is written for GPs and other health professionals running their own practices. It tells you in simple, engaging style what the pitfalls are and how to avoid them. It illustrates the good and bad ways of negotiating through management issues, using case examples and lightening the messages with witty cartoons. Written by a GP with over 10 years' experience editing a leading GP magazine, and an accountant whose firm advises over 2500 GPs, the information here is sound, relevant and up.